Risco de desenvolvimento de Melanoma em pacientes portadores de Nevo Melanocítico Congênito Gigante - Ana Carolina Leite Viana (2012)
BACKGROUND: Large congenital melanocytic nevus is defined as a melanocytic lesion present at birth that will reach a diameter 20 cm in adulthood. Its incidence is estimated in <1:20,000 newborns. Although it is recognized as a risk factor for the development of melanoma, the precise magnitude of this risk is still controversial. OBJECTIVES: To describe clinical and epidemiological data of patients seen at the Hospital das Clínicas, Federal University of Minas Gerais, and to assess the risk of development of melanoma in this population. METHODS: Our prospective cohort comprised patients with large congenital melanocytic nevi seen between July 1999 and July 2011. The following variables were analyzed: age at the enrollment in the study, gender, skin color, clinical features of the nevus, follow-up time, personal history of melanoma, clinical and laboratorial neurologic evaluation, presence of neurocutaneous melanocytosis, association with other cutaneous or extracutaneous disorders, therapeutic approach and family history of melanoma, multiple acquired nevi and congenital nevi. The cumulative risk for the development of melanoma (survival analysis) and the standardized morbidity ratio were calculated for those patients with at least one month of follow-up time. RESULTS: Sixty-three patients were enrolled. Six of them were excluded: one for presenting melanoma at the time of enrollment and five for insufficient follow-up time. The remainder 57 were followed for a mean time of 5.5 years (median: 5.2 years). The median age at the time of enrollment was 2.6 years and the sample showed an equivalent gender distribution (50.8% females). As to the skin color, 54.0% were caucasians, 41.3% mulatos and 4.7% blacks. The trunk was the most common location (69.8%) and 30.2% of the patients had bathing trunk nevi. Satellite lesions were observed in 84.1% of the individuals and no case of symptomatic neurocutaneous melanocytosis could be detected. The nevus was fully excised in three (4.8%) patients, partially removed in 11 (17.4%) and clinical observation alone was the approach in 49 (77.8%) patients. Melanoma was diagnosed in two (3.5%) individuals. The five-year cumulative risk was 4.8% (CI 95%: 1.9-11.5) and the standardized morbidity ratio (relative risk) was 1,584 (CI 95%: 266-5232; p < 0.001). CONCLUSIONS: Our data is similar to those of the literature as to the age at the time of enrollment, site of predilection of the nevi, satellite lesions and cumulative risk of melanoma. The early enrollment and the relatively long follow-up time render quality and confidence to our data base. Contrary to other reports, no female predominance was found in our cohort. Also, our study has a high number of patients with no therapeutic intervention, a suitable situation to better understand the natural history of these lesions. As previously reported, our findings demonstrate a greater risk of melanoma in patients with large congenital melanocytic nevi.